Hylaeus (Hylaeana) dominicalis, a new species and the first colletid bee recorded from Dominica, Lesser Antilles - Gibbs, Jason (Journal of Melittology, 2020)
A new species of colletid bee, Hylaeus (Hylaeana) dominicalis Gibbs, new species, is described and figured from the Commonwealth of Dominica. The new species can be distinguished from consubgeneric species in the Caribbean Islands based on the integumental coloration, facial fovea, and pubescence. A list of all known Hylaeus from the Caribbean Islands is provided.